2018
DOI: 10.1111/ced.13398
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of spinal cannabinoid receptors in the antipruritic effects of WIN 55,212-2, a cannabinoid receptor agonist

Abstract: Our findings support prior researches indicating that cannabinoids exert antipruritic effects. Moreover, our results show that the antipruritic effects of cannabinoids are partially mediated by spinal CB1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…106 Recently, it has been suggested that the antipruritic effects of cannabinoids are independent of descending inhibitory serotonergic pathways. 107…”
Section: Topical Cannabinoidsmentioning
confidence: 99%
“…106 Recently, it has been suggested that the antipruritic effects of cannabinoids are independent of descending inhibitory serotonergic pathways. 107…”
Section: Topical Cannabinoidsmentioning
confidence: 99%
“…The pathogenesis of pruritis is well researched and is described comprehensively in various recent review articles. [64][65][66] Though most of the ECS research indicates that the itch response is primarily modulated through CB1 receptors in the CNS, [67][68][69] some reports argue the involvement of peripheral CB1 receptors could also be a potent contributor to itch. 70,71 The available data thus far for the involvement of peripheral CB2 receptors are conflicting and more research is needed to conclusively determine its role in pruritis.…”
Section: Itch (Pruritis)mentioning
confidence: 99%
“…Attenuation of itching replies by augmenting endocannabinoid tonus via the inhibition of the endocannabinoid degradative enzymes, such as fatty acid amide hydrolase and monoacylglycerol lipase which is a different promising method for treating pruritus (14)(15)(16). Our research group also indicated that the synthetic cannabinoid agonist WIN 55,212-2 exerts dose-dependent antipruritic effects and this effect is partially mediated by spinal cannabinoid receptors CB1 (17,18).…”
Section: Systemic Cannabidiol Does Not Reduce Compound 48/80-induced Itching Behavior In Micementioning
confidence: 77%